Video Simulation-Based Basic Life Support Training and Changes in Knowledge and Attitudes among Junior High School Teachers: A Quasi-Experimental Study - Zulmah Astuti; Milkhatun Milkhatun; Rahma Amalia; Mellia Anata Tasya; Siti Khoiroh Muflihatin (Media Keperawatan Indonesia, 2026)
Out-of-hospital cardiac arrest (OHCA) remains a significant public health issue, with low rates of bystander basic life support (BLS) provision globally. Improving BLS preparedness among schoolteachers may contribute to strengthening early emergency response capacity. The objective of this research is to examine changes in knowledge and attitudes following video simulation-based basic life support training among junior high school teachers. A quasi-experimental one-group pre-post study was conducted among 30 purposively selected teachers from a public junior high school in Samarinda City. Knowledge and attitudes were measured using validated questionnaires before and after the intervention. Changes in categorical outcomes were analyzed using McNemar’s test, and effect size was calculated using Cohen’s w. Significant improvements were observed in both knowledge and attitudes after the training (p < 0.001). The proportion of teachers categorized as having adequate knowledge increased from 4.2% to 96.7%, while positive attitudes increased from 6.7% to 83.3%. A large effect size was identified (Cohen’s w = 0.856). However, given the absence of a control group, the observed improvements cannot be fully attributed to the intervention. Video simulation-based BLS training was associated with improvements in knowledge and attitudes among junior high school teachers. These findings suggest potential educational benefits; however, causal interpretations should be made cautiously due to the quasi-experimental design.